The analysis of the capacity of the selected measures of decision-making models in companies - Kościelniak, Helena; Skowron-Grabowska, Beata; Łęgowik-Świącik, Sylwia; Łęgowik-Małolepsza, Małgorzata (Copernican Journal of Finance & Accounting, 2015)
The paper aims at the analysis of the information capacity of selected instruments of the assessment of decision-making models in the analyzed companies. In the paper there are presented the idea and concepts of decision-making models. There have been discussed the selected instruments of the assessment of decision-making models in enterprises. In the final part of the paper there has been held the quantification of decision- making models in the investigated cement industry companies. To meet the objective of the paper there have been used literature studies and descriptive analysis. To specify the strength and direction of interactions between the parameters of the selected measures there has been calculated Pearson correlation coefficient. The problem of information capacity of the instruments of the assessment of decision-making models is important and up-to-date due to its impact on the effectiveness of management of the analyzed enterprises and the possibility to generate value added.